2020
DOI: 10.1111/bjdp.12335
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic vigilance online: Textual inaccuracy and children's selective trust in webpages

Abstract: In this age of 'fake news', it is crucial that children are equipped with the skills to identify unreliable information online. Our study is the first to examine whether children are influenced by the presence of inaccuracies contained in webpages when deciding which sources to trust. Forty-eight 8-to 10-year-olds viewed three pairs of webpages, relating to the same topics, where one webpage per pair contained three obvious inaccuracies (factual, typographical, or exaggerations, according to condition). The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Another potential possible explanation might be that in the current study, the designated specific information source provided inaccurate statements in all four trials and the ‘simplicity’ of this evidence may have caused older children to avoid using more sophisticated strategies to evaluate the reliability of the internet. Future studies may address this possibility by presenting online information which contains both accurate and inaccurate statements (Einav et al, 2020). Another potentially informative direction for future research would be to explore how children treat inaccurate information on the internet when it is embedded in a persuasive context, such as advergames and whether children apply the same heuristics that they use to evaluate persuasive messages in non‐internet contexts (Hudders et al, 2016; Van Reijmersdal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential possible explanation might be that in the current study, the designated specific information source provided inaccurate statements in all four trials and the ‘simplicity’ of this evidence may have caused older children to avoid using more sophisticated strategies to evaluate the reliability of the internet. Future studies may address this possibility by presenting online information which contains both accurate and inaccurate statements (Einav et al, 2020). Another potentially informative direction for future research would be to explore how children treat inaccurate information on the internet when it is embedded in a persuasive context, such as advergames and whether children apply the same heuristics that they use to evaluate persuasive messages in non‐internet contexts (Hudders et al, 2016; Van Reijmersdal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies suggest that young children are not effective at searching for information online (Dodge et al, 2011; Duarte Torres et al, 2014), nor do they apply the strategies that adults use to evaluate website credibility (Eastin et al, 2006; Mason et al, 2014; Metzger et al, 2015). For instance, Einav et al (2020) found that when confronted with conflicting information from different webpages, children ages 8–10 failed to reject information on the webpage with factual inaccuracies and exaggerations. However, the children recognized misinformation, suggesting that the challenge for them was paying attention to errors on webpages when seeking and endorsing novel information online.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Einav et al (2020) suggest that children may not be as sensitive and critical toward webpages with previous inaccuracies and will refer to them when seeking novel information. In their study, 8to 10-year-olds appeared to treat webpages with inaccurate information (e.g., "Polar bears have thick stripy fur") as similarly reliable and trustworthy as webpages presenting correct content, even when they were aware of the factual inaccuracies.…”
Section: Potential Mechanisms Underlying Children's On-screen Learningmentioning
confidence: 99%
“…Although children in the younger age group were expected to be familiar with information sources like the internet and computers (Dodge et al, 2011), older children were likely to have more experience forming their own search queries or using technology to obtain information (Duarte-Torres et al, 2014) and more likely to adapt their queries if met with dissatisfying or inaccurate answers from voice assistants (Oranç & Ruggeri, 2021). That said, given that skepticism of information sources increases across the elementary school years (Mills, 2013) and children ages 8-10 show some awareness that the internet includes inaccurate information (Einav et al, 2020), older children in our study might also show more skepticism of a voice assistant's responses than younger children.…”
mentioning
confidence: 99%
“…Between ages 5–6 and 7–8, children show an increasing preference for seeking and believing scientific and historical information provided by the internet (Wang et al, 2019). Nevertheless, even 7- and 8-year-old children do not show unmitigated trust in information received from the internet (Danovitch & Lane, 2020), and children as old as 10 years may struggle to determine whether information on webpages is accurate (Einav et al, 2020).…”
mentioning
confidence: 99%